ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN LANGKAH PEMECAHAN MASALAH POLYA - Ana - Rosydiana (MEJ (Mathematics Education Journal), 2017)
Purpose of this study is to describe the ability of student Class X-APK 2 SMK PGRI Dampit to solving the problem story based from problem solving step by polya. this research used descriptive-qualitative research. The result from this study explain that the student ability to solve the problem by polya step are different in each category. Students at high, medium and low category have been able to understand the meaning from every problem in the ability to make a plan, the student from high category have been able to make a plan, students from medium were not fully able to make a plan, beside the students from low category can’t make a single plan. The students ability to implement the plan can be seen from how students make a plan. Meanwhile the ability to make a review only student from higt category that can carry it out.